The battle of YouTube, TV and Netflix: an empirical analysis of competition in audiovisual media markets - Oliver Budzinski; Sophia Gaenssle; Nadine Lindstädt-Dreusicke (SN Business & Economics, 2021)
The world of audiovisual online markets is rapidly changing. Not long ago, it was dominated by linear television, transmitted terrestrially, through cable networks or via satellite. Recently, streaming services such as Netflix, YouTube, Amazon Prime and others have emerged as new suppliers of audiovisual content. In this quickly changing industry, competition interrelations between such different formats such as traditional TV, videos on YouTube, and streaming via Netflix are subject to controversy. In particular, doubt is cast on services such as YouTube exerting competitive pressure on services such as Netflix and traditional TV. Based upon a survey with 2920 participants, we provide an empirical analysis of consumption behavior of audiovisual contents. Using descriptive and analytical statistics, including multiple equation models, we show that there are specific areas within audiovisual content markets, where YouTube exerts considerable competitive pressure on both Netflix and classic TV, for instance, through prime time video entertainment. However, our analysis yields differentiated results as we also identify areas, where competition intensity between different service types appear to be low, for instance, through daytime and regarding the intention to shorten waiting time.
Keywords: L82; L86; Z10; M21; L13; L40; L51; C39; 330; Video-on-demand; Cultural economics; Television; Competition policy; Consumption behavior